Electrical Power Generation from Refrigerator Waste Heat Using Thermoelectric Generator for Small Device Charging - SAIDI, NUR AISYAH ASYIKIN; Nor Aira Zambri (Progress in Engineering Application and Technology, 2026)
This project aims to explore the potential of recovering waste heat from domestic appliances, specifically refrigerator condenser coils, to generate electrical power for low-power applications. Energy harvesting is achieved by utilizing the Seebeck effect through six thermoelectric modules (TEC1-12706) connected in series to maximize the total voltage output. The methodology involves the construction of a thermal sandwich structure consisting of an aluminum heat spreader plate, the Peltier modules and a finned heat sink equipped with an active cooling system (DC fan). A primary challenge in thermal transfer bridging the gap between the curved surface of the condenser coils and the flat surface of the modules was addressed through the application of high-conductivity thermal grease and a robust mechanical clamping system to minimize thermal resistance. The harvested electrical energy is processed via a DC-DC boost converter (XL6009) to stabilize the output at 5V, which is then used to charge 18650 Lithium-ion cells through a USB power bank module. Preliminary results indicate that the system is capable of generating sufficient voltage to charge mobile devices sustainably, relying solely on the temperature gradient between the refrigerator’s waste heat and the ambient air. This project demonstrates the feasibility of green energy harvesting concepts in improving energy efficiency within a residential environment.